Perspectives in biopolymer/graphene-based composite application: Advances, challenges, and recommendations - Asim N.; Su'Ait M.S.; Badiei M.; Mohammad M.; Akhtaruzzaman M.; Rajabi A.; Amin N.; Ghazali M.J. (De Gruyter Open Ltd, 2023)
Biocompatibility; Biodegradability; Biomolecules; Biopolymers; Hydrophobicity; Surface chemistry; Biopolymer; Composite applications; Graphene-based composites; Hydrophobic surfaces; Living creatures; Modification; Other properties; Physical and chemical properties; Property; Synergetic effect; Graphene